Supporting Open Practices with Teachers in Zambia - Kris Stutchbury (Commonwealth of Learning, 2019)
This paper demonstrates how the features and affordances of open learning have been developed in new and productive ways to provide school-based continuing professional development for teachers in Zambia. It presents and critically reviews data from 200 teachers who have taken part in phase 1 of the Zambian Education School-based Training (ZEST) – a project which, over the next three years, will be scaled-up across Zambia. The project is underpinned by the belief that knowledge about teaching is co-constructed through participation in, and reflection on, practice. Thus, the emphasis is on empowering teachers to work together to develop practices appropriate to their context – open practices. In the study, we describe an on-going process of realist evaluation which enables us to establish at an early stage what works in which contexts and informs on-going project planning. It concludes that this approach to evaluation has the potential to be helpful in understanding open practices and how they can be developed.